Literature Review: Perkembangan Teknologi dalam Pembelajaran IPA - Fitria Ningrum; Qurrotul Ainia; Aprilia Musfirah; Anisah Yasmin Kumalasari; Yamin Yamin (Yayasan Citra Dharma Cindekia, 2026)
Technological development has significantly influenced the science learning process. This study aims to examine the development of technology used in science education and its impact on students' learning processes and outcomes. The research employed a literature review method by analyzing 30 scientific articles published between 2023 and 2026, obtained through Google Scholar. The analysis was conducted through data collection, article selection, data reduction, and comparative analysis. The findings indicate that various technologies, including animated videos, interactive multimedia, learning websites, digital E-LKPD, and Augmented Reality (AR), have been widely implemented in science learning. These technologies contribute to improving students' learning motivation, conceptual understanding, learning outcomes, creativity, and scientific literacy. Furthermore, technology supports the implementation of innovative student-centered learning models. However, the integration of technology still faces challenges, such as limited facilities, internet access, and teachers' technological competencies. Therefore, adequate infrastructure support and continuous teacher professional development are necessary to optimize the use of technology in science education.